THEORETICAL FOUNDATIONS OF FOREIGN LANGUAGE LEARNING - Pulatova Sharipaxon Sobirjonovna (Bright Mind Publishing, 2025)
The issue raised in this essay is the most important result of studies that there are factors that help students succeed in the educational process with individualized learning methods. In this regard, the question arises: why do people differ so much from each other in the success of becoming proficient at a foreign language? In this article, we tried to find the answer for this question.
Keywords: Training, communication, emphasis, knowledge, motivation, native language, matrix method.